Gallbladder Hemorrhage Mimicking Acute Cholecystitis in a Patient under Antiplatelet Therapy - Choi, Y. S. (Zeitschrift für Gastroenterologie, 2012)
Hemorrhage within the gallbladder is rare but potentially fatal. It can be easily overlooked and misdiagnosed because of its low incidence and presentation that is similar to other types of hepatobiliary disease. We present an unusual case of gallbladder hemorrhage in a 36-year-old male patient who was taking antiplatelet medication following cardiac surgery. The patient was misdiagnosed with acute primary cholecystitis and, in consideration of postoperative complications with cardiovascular comorbities, serial treatment with urgent percutaneous transhepatic gallbladder drainage and delayed laparoscopic cholecystectomy was prescribed. Unexpectedly, a gallbladder hemorrhage was intraoperatively confirmed as the gallbladder appeared filled with dark blood clot-like materials. The patient recovered well and was discharged on the 3rd postoperative day without complications. In patients who are on antiplatelet therapy, gallbladder hemorrhage should be considered in the differential diagnosis if they have symptoms typical of biliary colic. In addition, delayed surgery with prompt biliary diversion may represent a safe and effective treatment approach.
Keywords: Gallenblase; Aggregationshemmer; Antikoagulans; Blutung; Hämorrhagie